Pengaruh Motivasi, Mata Kuliah Perpajakan dan Literasi Perpajakan Terhadap Minat Mahasiswa Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya dalam Berkarir di Bidang Perpajakan - Yakin, Achmad Ainul; Widayati, Irin (Jurnal Pendidikan Akuntansi (JPAK), 2022)
This research was conducted to determine the effect of motivation, taxation courses and tax literacy on the interests of FEB UNESA students in careers in taxation. This research uses purposive sampling method. The research sample consisted of 100 students from the Accounting, Accounting Education, Economics Education, Office Administration and Management study programs at the State University of Surabaya who had taken the taxation course program.. The research utilizes the main data obtained through the distribution of questionnaires in a google form format with a Likert scale. Data analysis through multiple linear regression. The outputs obtained, namely Motivation (X1), Taxation Courses (X2) and Tax Literacy (X3) have a large significant effect on the interest of FEB UNESA students in determining a career in taxation.